Six‐month respiratory outcomes and exercise capacity of COVID‐19 acute respiratory failure patients treated with continuous positive airway pressure. Issue 11 (18th November 2021) - Damanti, Sarah; Ramirez, Giuseppe Alvise; Bozzolo, Enrica Paola; Rovere‐Querini, Patrizia; De Lorenzo, Rebecca; Magnaghi, Cristiano; Scotti, Raffaella; Di Lucca, Giuseppe; Marinosci, Alessandro; Strada, Silvia; Di Terlizzi, Gaetano; Vitali, Giordano; et al.
ABSTRACT: Background: COVID‐19 long‐term sequelae are ill‐defined since only a few studies have explored the long‐term consequences of this disease so far. Aims: To evaluate the 6‐month respiratory outcome and exercise capacity of COVID‐19 acute respiratory failure (ARF) patients treated with continuous positive airway pressure (CPAP) during the first wave of the ongoing COVID‐19 pandemic. Methods: A retrospective observational study included COVID‐19 patients with ARF. Interventions included CPAP during hospitalisation and 6‐month follow up. Frailty assessment was carried out through frailty index (FI), pO2 /FiO2 during hospitalisation and at follow up, respiratory parameters, 6‐min walking test (6MWT) and the modified British Medical Research Council (mMRC) and Borg scale at follow up. Results: More than half of the patients had no dyspnoea according to the mMRC scale. Lower in‐hospital pO2 /FiO2 correlated with higher Borg scale levels after 6MWT ( ρ 0.27; P 0.04) at the follow‐up visit. FI was positively correlated with length of hospitalisation ( ρ 0.3; P 0.03) and negatively with the 6MWT distance walked ( ρ −0.36; P 0.004). Conclusions: Robust and frail patients with COVID‐19 ARF treated with CPAP outside the intensive care unit setting had good respiratory parameters and exercise capacity at 6‐month follow up, although more severe patients had slightly poorer respiratory performance compared with patients with higher PaO2 /FiO2 and lower FI.